China's Effort to Secure Strategic-Economic Project: Utilization of PSC to Secure Belt and Road Initiative - Nugroho, Bayu Fajar; Nurilham, Muhammad (Jurnal Ilmiah Muqoddimah: Jurnal Ilmu Sosial, Politik dan Hummaniora, 2024)
The existence of the Military or Private Security Industry at the moment is very sporadic and massive—with an estimate that it will continue to grow until 2028. China is not an exception, particularly in light of the initiative known as the Belt and Road Initiative (BRI), which aims to increase connectivity. The Belt and Road Initiative (BRI) is a highly ambitious undertaking, but it is not immune to the numerous issues that have emerged, particularly with regard to security. There have been multiple threats, and even attacks, against BRI projects and workers; as a result, China has had to take steps to resolve the issues. China eventually discovered a low-key means to ‘exist’ after ceasing to utilize its military due to restrictions imposed by the concept of non-interference. This paper is an explanatory research that tries to reveal the phenomenon that occurs by using the existing conceptual framework and operationalization of concepts. The hypothesis then is that the Chinese PSC contributes directly to safeguarding BRI assets and employees, which then gives rise to new findings and trends in the Military or Private Security Industry, namely PSC with Chinese-Characteristics.